1996
DOI: 10.1159/000217260
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with Recombinant Factor VIla in Patients with Thrombocytopenia

Abstract: Platelets play a central role in primary hemostasis. The role of the coagulation mechanism during early stages of hemostasis is less clear, although increasing evidence is emerging indicating the ultimate importance of the factor VII (FVII)-tissue factor-dependent coagulation system in providing the first thrombin molecules necessary for the platelet activation to occur. Supporting this, early fibrin formation has been reported to occur within the bleeding time wound and infusion of recombinant FVIIa (rFIIa) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
1
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(144 citation statements)
references
References 6 publications
(6 reference statements)
7
131
1
5
Order By: Relevance
“…Thus, the effect observed in all responsive patients and cases can not be solely attributed to rFVIIa. On the other hand, there are a number of reports describing the successful use of rFVIIa to stop bleeding in patients with nonimmune thrombocytopenia [20,27,28,42]. These studies indicate that rFVIIa is effective in the treatment of bleeding in patients with thrombocytopenia and/or thrombocytopathy, without a combination with other hemostatic agents.…”
Section: How Rfviia May Improve Hemostasis In Itpmentioning
confidence: 99%
“…Thus, the effect observed in all responsive patients and cases can not be solely attributed to rFVIIa. On the other hand, there are a number of reports describing the successful use of rFVIIa to stop bleeding in patients with nonimmune thrombocytopenia [20,27,28,42]. These studies indicate that rFVIIa is effective in the treatment of bleeding in patients with thrombocytopenia and/or thrombocytopathy, without a combination with other hemostatic agents.…”
Section: How Rfviia May Improve Hemostasis In Itpmentioning
confidence: 99%
“…It has also been successfully used for the treatment of bleeding in patients with congenital or acquired thrombocytopathies [5À8]. A preliminary phase I/II study demonstrated that rFVIIa reduced the bleeding time in 55 out of 105 patients with thrombocytopenia of various causes [9]. Furthermore administration of rFVIIa to a small cohort of 8 patients with thrombocytopenia and active bleeding resulted in eective hemostasis without any adverse eect [9].…”
Section: Introductionmentioning
confidence: 99%
“…Novel therapies such as rFVIIa, perhaps combined with antifibrinolytic agents, may result in improved outcomes, particularly in view of recent data documenting the efficacy of rFVIIa in both FVII-deficient and thrombocytopenic patients. [30][31][32] In conclusion, we describe an uncommon form of acquired coagulopathy arising as a complication of highdose chemotherapy and SCT, which contributed to the early demise of several patients undergoing this therapy. Further studies are needed to clearly elucidate the mechanism of this coagulopathy and whether patients with associated bleeding might be candidates for therapy with novel hemostatic agents.…”
Section: Discussionmentioning
confidence: 99%